2021
DOI: 10.1111/jcmm.16444
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification by long non‐coding RNAs profiling in COVID‐19 patients

Abstract: Coronavirus disease 2019 (COVID‐19), caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has become a global pandemic worldwide. Long non‐coding RNAs (lncRNAs) are a subclass of endogenous, non‐protein‐coding RNA, which lacks an open reading frame and is more than 200 nucleotides in length. However, the functions for lncRNAs in COVID‐19 have not been unravelled. The present study aimed at identifying the related lncRNAs based on RNA sequencing of peripheral blood mononuclear cells from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Previous studies have confirmed that lncRNAs are differentially expressed in patients with SARS-CoV-2, which are closely related to the occurrence and development of the disease. Cheng J et al reported altered lncRNAs between severe COVID-19 patients, non-severe COVID-19 patients and healthy controls (100). The findings showed that lncRNA GATA5 was significantly elevated in severe condition, indicating that the expression level of GATA5 was positively correlated with COVID-19 severity.…”
Section: Lncrna As a Diagnostic Biomarkermentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have confirmed that lncRNAs are differentially expressed in patients with SARS-CoV-2, which are closely related to the occurrence and development of the disease. Cheng J et al reported altered lncRNAs between severe COVID-19 patients, non-severe COVID-19 patients and healthy controls (100). The findings showed that lncRNA GATA5 was significantly elevated in severe condition, indicating that the expression level of GATA5 was positively correlated with COVID-19 severity.…”
Section: Lncrna As a Diagnostic Biomarkermentioning
confidence: 98%
“…Cheng J et al. reported altered lncRNAs between severe COVID-19 patients, non-severe COVID-19 patients and healthy controls ( 100 ). The findings showed that lncRNA GATA5 was significantly elevated in severe condition, indicating that the expression level of GATA5 was positively correlated with COVID-19 severity.…”
Section: The Application Prospects Of Lncrnas In Diagnosis and Treatmentmentioning
confidence: 99%
“…OSCC is one of the most common malignancies worldwide ( 1 ). Although many risk factors, such as alcohol addiction and HPV infections, have been reported to be involved in the tumourigenesis and progression of OSCC ( 15 ), genomic mutations in PTEN and AKT lead to the uncontrolled phosphorylation of AKT and thus promote the proliferation of OSCC ( 16 , 17 ). Oncogenic amplification, such as in the epidermal growth factor receptor promotes the activation of downstream signaling and eventually promotes OSCC survival ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the transcript levels of VDR, CYP27B, SNHG6, SNHG16, Linc00511 and Linc00346 can differentiate patients from controls with high specificity (Nicknafs et al, 2021; Taheri et al, 2021 ). Another lncRNA panel consisting of AC010904.2, AC012065.4, AL365203.2, AC010175.1, LINC00562, AC010536.1 and AP005671.1 presents a good differential ability between severe and nonsevere COVID-19 patients ( Cheng et al, 2021 ).…”
Section: Lncrnas and Sars-cov-2 Infectionmentioning
confidence: 99%